THE INFLUENCE OF THE ROOTS OF THE TRANSFER NUMBER ON THE QUALITY INDICATORS OF THE TRANSITION PROCESS OF DISCRETE STABILIZATION SYSTEMS - Мовчан, С. Л. (Proceedings of National Aviation University (archive), 2021)
The influence of the roots of the numerator of the transfer function of a discrete stabilization system on the duration and oscillation of the transient process is considered. Based on the obtained expressions, it is shown that the oscillation and duration of the corresponding components of the transient process are the same in the presence and absence of the roots of the numerator of the transfer function of the discrete stabilization system and depend on the roots of the characteristic equation. indirect root methods of quality assessment.